1431 Asynchronous, online training of healthcare workers and hygiene/safety managers in occupational health and hygiene. (24th April 2018) - Forst, Linda; Nickels, Leslie; Zalk, David; Zanoni, Joseph
Abstract : Background: The Global Program in Occupational Health Practice (GPOHP) is a 400 hour, online, interactive program with 2 tracks in Health and Hygiene. GPOHP has trained 135 individuals from 85 different countries over 8 years. Methods: An online survey of course participants was administered to determine the value of this training and to guide future content and training methods. Results: 30% of the prior course participants from 19 countries responded. 68% received company sponsorship for tuition, 19% received scholarships and 13% were self-funded. Respondents reported a significant increase in knowledge base, greater confidence in doing their jobs, clarity about where to seek the best resources, awareness of global standards, and how to execute specific activities including, incident (accident) investigation, noise monitoring, ergonomic assessment, return to work after injury/illness, and development of a worker screening program. A few described moving up in their careers because of this training. Several participants continue to share ideas and plans with their classmates across national boundaries. Discussion: Online training in OH is an important and apparently successful tool for training those without locally available courses. Asynchronous communication lowers expenses by reducing time off work and out-of-country. Hands on activities applied in their own work settings with feedback from experts were likely to be key in developing relevant and immediately applicable skills. Establishing a network of OH providers could improve conditions for workers and companies, globally.